2018
DOI: 10.3139/217.3439
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic Blends of PP and Waste Rubber Powder: Effects of Compatibilizer on Tensile Properties, Thermal Behavior and Decomposition Kinetics

Abstract: To improve the performances of waste rubber powder filled polypropylene (PP/WRP) blends, WRP was modified by γ-aminopropyltriethoxysilane (APTES) via mechano-chemical method, and then maleic anhydride (MAH) grafted PP (mPP) and MAH grafted ethylene-α-octene copolymer (mEOC) were chosen as the interfacial compatibilizers. The PP/WRP blends were prepared by melt-compounding and compression, and their morphological structures, tensile properties and thermal behavior were investigated carefully. Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…With the assistance of a suitable compatibilizer, the compounds can be rid of phase separation [23]. Yang et al indicated that maleic anhydride grafted polypropylene is a useful compatibilizer to improve the interphase problem between polypropylene and wasted rubber powder [24].…”
Section: Introductionmentioning
confidence: 99%
“…With the assistance of a suitable compatibilizer, the compounds can be rid of phase separation [23]. Yang et al indicated that maleic anhydride grafted polypropylene is a useful compatibilizer to improve the interphase problem between polypropylene and wasted rubber powder [24].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Reuse has been encouraged to overcome the environmental impacts caused by this kind of waste and, consequently, contributing to a sustainable environmental cycle. [4][5][6] The reuse of postconsumer and postindustrial rubber waste is a major challenge, particularly in the tire and footwear industries, since they are mostly vulcanized. One of the main obstacles in the recycling of vulcanized rubbers is the fact that these materials have cross-links in their structure, preventing their melt and reprocessing.…”
Section: Introductionmentioning
confidence: 99%